KONTRIBUSI KETERAMPILAN MEMBACA TEKS CERITA FABEL TERHADAP KETERAMPILAN MENULIS TEKS CERITA FABEL SISWA KELAS VIII SMP NEGERI 35 PADANG - Astuti, Juli; Asri, Yasnur (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTÂ The purpose of the study is to describe the skill of reading Fable Story Texts on Writing Skills for Fable Story Texts of Class VIII Students of SMP Negeri 35 Padang. This type of research is quantitative with descriptive method. The design used in this study is design contribution. The population of this study was the eighth grade students of SMP Negeri 35 Padang who were enrolled in the 2019/2020 school year, namely as many as 134 students. The sample in this study was determined by proportional random sampling of 25% of the population, namely 35 students. The data of this study were in the form of scores on the results of the test skills for reading fable text and tests of fable story writing skills. The data was obtained through two types of tests namely objective tests to measure the skill of reading fable story texts and performance tests to measure the writing skills of fable stories. The results of this study are three. First, the ability to read fable story texts in class VIII Padang Public Middle School 35 is in good qualification (B) with an average value of 77.55. Second, the skill to write fable story texts in grade VIII Padang Public Middle School 35 is in good qualification (B) with an average value of 73.97. Third, there is a contribution to the contribution of fable's text reading skills to the fable writing text skills of Grade VIII students of Padang State Middle School at 67.57%. It was concluded that the skill to read fable story texts contributed to the skill of writing fable story texts.Â Kata kunci: Kontribusi, Keterampilan membaca, Menulis, Teks Cerita Fabel